Development of new control algorithms for high performance autopilots - Raman, Akshay (2015)
The project simulates dynamics of an aircraft subjected to an external environment that has a direct impact on the stability and behaviour of the aircraft. The Eurofighter Typhoon 2000 was chosen as the reference aircraft for the course of the project. The aircraft was subjected to open loop testing using MATLAB/Simulink on the nonlinear system of equations formulated by using the general six degree of freedom set of equations for an aircraft moving through space. Stability derivatives for these equations were obtained from the TORNADO Toolbox using the general geometry of the wing and simulating it as a flat plate. Using a reference input signal, such as a general sinusoid, the PID Controllers with predefined control algorithms are defined and their working is visually depicted using an open source flight simulator software such as FlightGear. A trajectory is then defined for the aircraft to follow and the results are visualized using the six degree of freedom simulation platform. The main purpose of the project is to optimize controller performance for a given trajectory and to be able to predict and control the response of an aircraft to external stimuli from the environment. The adaptability of these controllers to stimuli is an area of further study in this field and provides significant opportunities for future research. Aircrafts are constantly under the influence of external unbalanced forces depending upon the ever changing environment around them (such as weather) or depending on the manoeuvres that need to be executed at various stages of the mission profile of the aircraft. Thus it is important to gain insight into and be able to gauge and counteract these external influences on the aircraft.